Molecular and Phenotypic Expansion of Alström Syndrome in Chinese Patients - Zhang, Qianwen; Ding, Yu; Feng, Biyun; Tang, Yijun; Chen, Yao; Wang, Yirou; Chang, Guoying; Liu, Shijian; Wang, Jian; Li, Qian; Fu, Lijun; Wang, Xiumin (Frontiers in Genetics, 2022)
Alström syndrome (ALMS) is a rare inherited metabolic disease and ciliopathy. Large cohorts of ALMS are lacking around the world. Detailed genetic and phenotypic data were obtained from all affected individuals. Olfactory function was evaluated by the Chinese Smell Identification Test and facial pattern was analyzed with Face2gene. Fifty ALMS patients were included in this study, aged from 0.3 to 21.7 years old. Sixty-one ALMS1 variants in 50 patients from 47 different families were confirmed, including 59 truncating and 2 exon deletions. Twenty-four of those variants were novel. We also summarized all previously reported cases of Chinese ALMS patients (69 patients) and identified specific and common variants within the Chinese population. Besides, the Chinese Smell Identification Test scores in patients was lower than that in controls (11.97 Vs 10.44, P < 0.05), indicating olfactory identification impairments in ALMS patients. The facial pattern in ALMS patients was also distinctive from that of the controls (P < 0.05). In conclusion, this is the largest cohort of Chinese ALMS patients. We have successfully identified both specific and common variants in our cohort.